A Note on Bidi Leaf (Diospyros Melanoxylon) - Desarkar, B. K. (Indian Forester, 1963)
The leaf of Diospyros melanoxylon (tendu) is universally used for making bidi, an indigenous form of smoke. It is an important economic minor forest product that brings substantial revenue to the Forest Departments of certain States notably Orissa, Madhya Pradesh, and Andhra Pradesh. Here, an attempt has been made to collect the up-to-date information on the bidi leaf industry in India. The species used for bidi leaf, their distribution in different States, quality of leaves, pollarding, coppicing, method and cost of exploitation, revenue, etc. have been described in this article.